Influence of Rearing Substrates and Nontarget Hosts on the Bionomics of the Tachinid Parasitoid Nemorilla maculosa (Diptera: Tachinidae). Issue 2 (15th February 2018) - Agbessenou, Ayaovi; Tounou, Agbéko Kodjo; Dannon, Elie Ayitondji; Datinon, Benjamin; Agboton, Cyriaque; Srinivasan, Ramasamy; Pittendrigh, Barry Robert; Tamò, Manuele
Abstract: The tachinid Nemorilla maculosa Meigen (Diptera: Tachinidae) was introduced from Taiwan to Benin for evaluating its potential as a biocontrol candidate against the cowpea pest Maruca vitrata (Fabricius) (Lepidoptera: Crambidae). To optimize its rearing, we assessed the influence of M. vitrata larval age and rearing substrate—cowpea germinating grains and peabush leaves—on its life table parameters, while its host specificity was investigated with regard to nontarget effects. Parasitism rates were higher when older larvae (10- and 14-d old) were offered to females of N. maculosa compared to the younger (2-, 4-, and 6-d old) host larvae. Regardless of the rearing substrate, development time was longer for females than males, and females lived longer than males irrespective of the age of the host. Sex ratio did not vary significantly with host ages or rearing substrate. The average number of eggs laid by a female reared from M. vitrata larvae feeding on cowpea germinating grains or peabush leaves was 94.2 ± 4.38 and 71.9 ± 1.70 eggs, respectively. The host suitability of N. maculosa was assessed by testing four nontarget Lepidoptera species: Spodoptera littoralis Boisduval (Lepidoptera: Noctuidae), Sesamia calamistis Hampson (Lepidoptera: Noctuidae), Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae), and Eldana saccharina Walker (Lepidoptera: Pyralidae). Larvae of S . littoralis and C. cephalonica were successfully parasitized while N. maculosa did not develop in the larvae of E. saccharina and S. calamistis although they were parasitized. Despite the potential of N. maculosa as a biological control agent against the pod borer M. vitrata, more detailed nontarget studies, extending to other native Crambidae species, are needed before making decisions on field releases.